Simultaneous Repair of Cleft Hard Palate by Vomer Flap along with Cleft Lip in Unilateral Complete Cleft Lip and Palate Patients. (9th December 2012) - Ferdous, Kazi Md. Noor-ul; Saif Ullah, M.; Shajahan, M.; Mitul, M. Ashrarur Rahman; Islam, M. Kabirul; Das, Kiorsh Kumar; Mannan, M. A.; Rahman, M. Junaed; Biswas, Sanjoy; Salek, A. J. M.; Das, Bijoy Krishna
Abstract : The purpose of the study was to see the short-term outcome of simultaneous repair of cleft lip and cleft hard palate with vomer flap against cleft lip repair alone in patients with unilateral complete cleft lip and palate (UCLP). A prospective observational study was carried out in 35 patients with unilateral complete cleft lip and palate who under-went cleft lip and cleft hard palate repair with vomer flaps simultaneously. After 3 months, cleft soft palate was repaired. During 1st and 2nd operations, the gap between cleft alveolus and posterior border of the cleft hard palate was measured. Postoperative complications, requirement of blood transfusion during the operation, and duration of operations were also recorded. Simultaneous repairs of cleft lip and closure of cleft hard palate with vomer flaps are easy to perform and are very effective for the repair of cleft lip and palate in UCLP patients. No blood transfusion was needed. Gaps of alveolar cleft and at the posterior border of hard palate were reduced remarkably, which made the closure of the soft palate easier, decreased operation time, and also decreased the chance of oronasal fistula formation.